Bilingualism and attitudes: A comparative study of foreign language learning dispositions - Orak, Suheyla Demirkol (Malque Publishing, 2026)
Bilingualism has emerged as an indispensable competency in the contemporary globalized landscape of the twenty-first century, with extant literature underscoring the multifaceted cognitive and sociolinguistic advantages associated with bilingual proficiency. In the Turkish educational context, English proficiency constitutes a paramount objective, given its status as the lingua franca of international commerce and academia, while empirical investigations have demonstrated that learners' attitudes substantially influence foreign language acquisition outcomes, yet the relationship between bilingual status and attitudinal orientations toward English language learning remains inadequately explored. This investigation examined whether bilinguals and monolinguals demonstrate differential attitudes toward English language acquisition, with the sample comprising 80 participants (43 Arab-Turkish bilinguals and 37 Turkish monolinguals) recruited via convenience sampling, and data collection employed Cook's Language Attitude Questionnaire, encompassing six dimensions addressing social, psychological, and personal facets of language attitudes. Independent samples t-test analyses revealed that although bilingual learners demonstrated a significantly higher overall attitude score toward English language learning, the cluster-level analyses showed no statistically significant differences across the social, psychological, or personal dimensions of the questionnaire (p >.05). These results indicate that bilingual status alone does not uniformly predict more favorable attitudinal orientations, suggesting instead that learners’ dispositions toward English are shaped by a broader constellation of contextual, motivational, and identity-related factors rather than by linguistic background in isolation. In line with this interpretation, the findings underscore the importance of adopting pedagogical practices that foster supportive, inclusive, and identity-affirming learning environments for all students, rather than assuming inherent attitudinal advantages among bilingual individuals. Consequently, future research would benefit from longitudinal and mixed-methods designs to more fully capture the dynamic and multifaceted processes underlying attitude formation and to illuminate how sociocultural positioning, educational experiences, and learners’ evolving identities influence their engagement with foreign language learning. © 2026, Malque Publishing. All rights reserved.
Keywords: foreign policy; monolingualism; motivation; multilingualism